Superficial corneal foreign body (FB) removal with magnifying loupe versus slit lamp and the effect of patching versus without patching-A comparative study (Journal of Dhaka National Medical College & Hospital, 2015)
Purpose To observe the outcome of superficial corneal foreign body removal with Slit lamp & Magnifying Loupe, effect of healing and pain relief with or without patching.Methods A prospective random study was conducted at Dhaka National Medical College from 01 January- 2012 to 31st December-2014. 200 eye of 150 patients who presented with superficial corneal FB in Ophthalmology department were studied. Inclusion criteria includes only superficial corneal FB. Exclusion criteria were conjunctival foreign body, Intraocular foreign body, patients below 10 yrs age. Verbal consent was obtained.Observation parameters included Superficial corneal foreign body removal with slit lamp 100(50%) and by magnifying loupe 100(50%) and using 26g hypodermic needles. All foreign bodies removed under topical anesthesia. Half of the patients were provided with eye patch and half without patch.                                                                                                                                   Result Male were 144 (96%) and rest female. 120 (80%) of the patients are 15-40 years. Rust mark remain 20(10%) eyes with loupe removal. Two cases developed dimness of vision due to corneal scar. Time of resolution was 5.35±1.52 days. Three patients developed infectious keratitis. Most patients 96(64%) attempted to remove FBS by themselves. Scar marks were more in self removal as wel as loupe removal group. Healing time was same in both types but pain relives was more in with patching. Patching was more effective in abrasion of more than 10 mm size. Patch causes loss of binocular vision temporarily but fill better then without patch.Conclusion Slit lamp removal is better in case of metallic FB, since the rust can be removed meticulously. Post removal patch and without patch had same effect on healing but pain relief was better with patching.J. Dhaka National Med. Coll. Hos. 2015; 21 (02): 51-54